2018
DOI: 10.1073/pnas.1712879115
|View full text |Cite
|
Sign up to set email alerts
|

Infected erythrocytes expressing DC13 PfEMP1 differ from recombinant proteins in EPCR-binding function

Abstract: SignificanceSequestration of Plasmodium falciparum-infected erythrocytes (IEs) in the brain microvasculature underlies the pathology of cerebral malaria. Parasites that express P. falciparum erythrocyte membrane protein 1 of domain cassette (DC) 8 and DC13 types bind to brain endothelial cells. Recent studies, largely based on recombinant proteins, have identified endothelial protein C receptor (EPCR) as the key receptor for endothelial cell binding. Using DC8- and DC13-expressing IEs, we show that binding of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
32
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(36 citation statements)
references
References 37 publications
1
32
0
2
Order By: Relevance
“…This indicates that EPCR is a major component of cytoadherence to HBMEC in CM, but not necessarily as the only primary receptor, as suggested by a recent study (Azasi et al, 2018). While positive correlations provide straightforward evidence for associations, negative correlations can also be informative.…”
Section: Discussionmentioning
confidence: 62%
See 2 more Smart Citations
“…This indicates that EPCR is a major component of cytoadherence to HBMEC in CM, but not necessarily as the only primary receptor, as suggested by a recent study (Azasi et al, 2018). While positive correlations provide straightforward evidence for associations, negative correlations can also be informative.…”
Section: Discussionmentioning
confidence: 62%
“…Paired analysis showed that there was no significant reduction in binding of UM isolates to HDMEC in the presence of rEPCR, indicating that EPCR does not play a major role in the adhesion of the UM isolates to HDMEC. EPCR binding by IE expressing the DC13 and DC8 variants has recently been questioned with data showing that DC13 expressing IE do not bind EPCR in vitro and binding of DC8 expressing IE to EPCR and brain endothelium was reduced in the presence of 10% human serum (Azasi et al, 2018). This effect of human serum was not seen with three patient isolates and It4var19 in our assay (Appendix Fig S2).…”
Section: Discussionmentioning
confidence: 69%
See 1 more Smart Citation
“…Adding on to previous reports, Storm et al attempted to recapitulate in the small in vitro flow chambers how parasites expressing different var genes lead to different clinical outcomes by comparing their binding abilities to brain or dermal endothelial cells through CD36, ICAM‐1 and EPCR. Importantly, Storm et al use in their assays iRBCs in the 1 st –3 rd cycle after blood collection expressing the native full‐length PfEMP1s, and endothelial cell lines naturally expressing their receptors, avoiding possible affinity artefacts introduced by analyses of individual recombinant PfEMP1 domains on plates coated with recombinant protein (Azasi et al , ). The data obtained are indeed supportive of EPCR being an important endothelial receptor responsible for iRBCs binding in cerebral malaria cases, alongside ICAM‐1 (Storm et al , ).…”
Section: Binding Properties Of Different Plasmodium Falciparum Clinicmentioning
confidence: 99%
“…The issues with these kinds of studies are further compounded by the enormous technical challenge of fully taking into account individuals’ exposure histories and therefore their immune status at the time of infection. This means that caution has to be exercised when trying to infer causality, which was recently re-emphasized by Azasi et al ., who found that in vitro iRBC binding to endothelial cells is often independent of EPCR and can easily be interrupted under flow conditions 27 . Approaches to gain a better understanding of the host–parasite interaction in capillaries include (1) improved understanding of the parasites actually responsible for pathology through direct sampling of sequestered parasites in different tissues by either using skin biopsies in patients 28 or sampling from tissues post-mortem 29 ; (2) improved assessment of parasite sequestration in tissues through direct observation of parasites within capillaries through mucosal surfaces to correlate capillary congestion with disease outcome 30 ; (3) seeking associations between peripheral parasite gene expression levels and direct measures of sequestration through malarial retinopathy 25 , 31 ; and (4) improved understanding of the role of NAI in shaping the infecting parasite population by seeking associations between peripheral parasite gene expression levels and pre-existing antibody responses in controlled human infections of volunteers with differing levels of natural exposure to infection 32 .…”
Section: What Causes Severe Malaria?mentioning
confidence: 99%